Evaluation of the policy effects of strong maritime country construction in China - Zhang, Kuncheng; Wang, Shiqing; Zhang, Xiaohan; Wang, Yingying; Bian, Jiayu; Tian, Shizheng (Frontiers in Marine Science, 2025)
Since the proposal to build a strong maritime country in 2012, China’s marine economy has developed rapidly. This study, using panel data from nine southeastern coastal provinces (1999-2023), employs methods such as the hybrid control-weighting model, kernel density estimation, and factor detection to evaluate the policy effects of building a strong maritime country on coastal regions. Fujian Province exhibits the strongest policy effect, whereas Hainan Province shows a weaker effect due to a narrow industrial structure and lagging technological innovation. Marine informatization is the core driver (q = 0.964), it enhances outcomes through marine technological innovation and industrial optimization. Marine technological innovation and tertiary sector optimization account for 92.6% and 76.9% of the explanatory power, respectively, emphasizing their role in high-quality marine economic development. The study suggests that future policies should focus on enhancing informatization, technological innovation, and optimizing the tertiary sector to advance the construction of a strong maritime country.